Avaliação laboratorial e produtiva de bovinos confinados, alimentados com feno de Brachiaria sp. e suplementados com antioxidantes - Costa, Gustavo Lage (2014)
The grass Brachiaria sp. brought to Brazil in the green revolution, came with the goal of increasing the Brazilian livestock production. The introducing of the grass, starts emerging problems such as leaf hopper pastures and hepatogenous photosensitization. The etiology of photosensitization caused by Brachiaria sp. is still controversial. But not even knowing for sure rightly if the cause is the steroidal saponins or the fungus Phytomices chartarium, it is known that they occur and cause damage to livestock. The described laboratory abnormalities are increased activity of enzymes aspartate aminotransferase (AST) and gamma glutamyl transferase (GGT), bilerrubinemia and jaundice, and evidence of insufficient functionof.liver. Histopathological examination can demonstrate a cholangiohepatitis and presence of foamy macrophages. The presence of these cells is important because its quantification was negatively correlated with the gain in cattle weight. Thus this study evaluated 40 Nelore young bulls, with the Brachiaria sp hay consumption adjusted to the maximum amount of forage (84%), with the goal of reproducing the hepatic abnormalities described in cases of photosensitization. Therefore, the aim of this study was to evaluate the possible liver changes, by the metabolic and histological profile of the liver and lymph nodes, and also check if the offered antioxidants would be able to minimize these changes, promoting greater weight gain and improving carcass characteristics of feedlot cattle. As a result, the braquiaria hay with low amounts of saponin and fungal spores did not induce clinical signs of liver damage in young bulls, but laboratory assessments indicate evidence of chronic inflammatory liver change with the presence of foamy macrophages. The antioxidant supplementation did not alter the metabolic profile of the animals, but reduced the amount of foamy macrophages in the liver. However this decrease did not improve weight gain of cattle, carcass characteristics and the final quality of the meat.